Fibrin Monomer and Systemic Lupus Erythematosus Reactivation During Pregnancy: A Retrospective Study - Tran Thi Kieu My; Hoang Thi Ha; Nguyen Huu Truong; Dao Thi Thiet; Nguyen Khanh Ha; Tran Dang Xoay; Linus Olson; Bach Quoc Khanh (Diseases)
Background: Pregnancies in patients with systemic lupus erythematosus (SLE) have always been considered high-risk. D-dimer is known for its role in excluding the diagnosis of thrombosis and has been associated with lupus reactivation; however, its physiological elevation during pregnancy limits its utility in this population. Fibrin monomer (FM) has been shown in multiple studies to remain stable in pregnant women. The objectives of this study were to evaluate D-dimer and FM levels, as well as to assess the role of FM in SLE activity during pregnancy. Methods: The subjects included 76 pregnant women with SLE diagnosed according to the Systemic Lupus International Collaborating Clinics (SLICC) 2012 criteria. The assessment of disease activity was in accordance with the Systemic Lupus Erythematosus Pregnancy Disease Activity Index (SLEPDAI). Results: The log10-transformed D-dimer (LtDD) and FM (LtFM) concentrations in the pregnant women with lupus were 1.229 (0.722–1.953) and 4.17 (3.01–5.34) µg/mL, respectively. A multivariate regression indicated that 59.1% of the variation in LtDD was influenced by the gestational age and SLEPDAI, while only 18.3% of the fluctuation in LtFM was affected by these factors. The concentration of LtFM was an independent factor in predicting SLE flare and disease activity level according to the SLEPDAI in pregnant women. Conclusions: In conclusion, this study’s findings suggest that elevated levels of both D-dimer and FM were observed in pregnant patients with SLE. However, only FM levels can be used as a prognostic factor in assessing the risk of SLE reactivation during pregnancy.